Polypill in Cardiovascular Disease Prevention: Efficacy and Perspectives - Fayzullaeva, Shakhlo; Khamidullaevav, Gulnoza; Abdullayeva, Guzal; Yusupova , Khafiza (CARDIOLOGY OF UZBEKISTAN, 2025)
Cardiovascular diseases (CVDs) are among the leading causes of morbidity and mortality worldwide. To enhance the effectiveness of prevention, the concept of a polypill containing multiple active pharmaceutical components has been introduced. This review explores the role of the polypill in primary and secondary prevention, along with its advantages and limitations. In primary prevention, the polypill may help reduce the risk of developing hypertension, dyslipidemia, and thrombosis. In secondary prevention, it aids in lowering the likelihood of recurrent cardiovascular events such as myocardial infarction and stroke. Additionally, the polypill improves medication adherence and reduces overall healthcare costs